Impact of heat on the deterioration of facades of the industrial heritage of the Peruvian Sierra - Lajo Cuno, César; Quispe Zapata, Rodrigo; Delgado Meneses, Patricia C.; Ibárcena Ibárcena, Valkiria (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
Urban heat and environmental pollution contribute to the deterioration of architectural heritage. Therefore, this research aims to analyze the impact of climatic, social, and environmental urban variables on heritage façade materials in three phases: identification of damage indexes based on materiality, observational flow analysis, and analysis of climate variability and wind chill using a thermographic camera and hygrometer. The results show that wood and ignimbrite are the materials most affected by heat and pedestrian behavior influences pedestrian traffic, choosing alternative routes to avoid discomfort caused by wind chill. This study aims to contribute to material analysis and develop conservation strategies for these types of heritage façades, addressing current environmental challenges and ensuring their durability over time.